Online Media Program Production and Marketing Process - Ritonga, Mahzura Alfirah; Kustiawan, Winda; Salsabila, Khalishah; Fajar, Khairul; Nisa, Khairun; Ritonga, Novendra Hariyadi; Auliya, Tadzkiya (Lembaga Riset Mutiara Akbar, 2025)
The process of radio production and the marketing of online media programs are interconnected in the modern media industry, starting with the planning of engaging content, recording, and editing to ensure optimal audio quality. Digital marketing strategies, including social media and collaboration with influencers, are essential for reaching new listeners and building a community. Understanding trends and audience preferences is also crucial in developing relevant programs. This research employs a literature review method to analyze the challenges and opportunities in the production and marketing of radio programs, demonstrating that the synergy between these two aspects and the utilization of modern technology are vital for creating engaging content in the digital era